2019
DOI: 10.17221/27/2019-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Association of polymorphisms in the GH and GHR genes with growth and carcass traits in rabbits (Oryctolagus cuniculus)

Abstract: In rabbits, growth and carcass traits are important for the breeding programme. An increasing number of annotated polymorphisms demands validation of their influence on those traits before they can be implemented in breeding practice. Therefore, the aim of this study was to investigate GH c.-78C>T, GHR c.106G>C polymorphisms in the population of Belgian Giant Grey, Termond White, and a crossbreed between New Zealand White and Belgian Giant Grey (NZW × BGG) rabbits. In total 379 animals were genot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 15 publications
1
7
1
Order By: Relevance
“…This fact is demonstrated by the higher muscularity of hind legs in final commercial crossbred H rabbits. The hind leg meat yield of rabbit genotypes in the present study was similar to that reported for the Belgian Giant Grey and Termond White rabbits [ 28 ]. In the case of LTL muscles, their yield was also slightly higher in H rabbits than in MS sired rabbits (7.8 vs. 7.5% of SW, respectively) and a higher LTL yield was found in H females than in MS sired females (7.8 vs. 7.3%, resp.).…”
Section: Discussionsupporting
confidence: 88%
“…This fact is demonstrated by the higher muscularity of hind legs in final commercial crossbred H rabbits. The hind leg meat yield of rabbit genotypes in the present study was similar to that reported for the Belgian Giant Grey and Termond White rabbits [ 28 ]. In the case of LTL muscles, their yield was also slightly higher in H rabbits than in MS sired rabbits (7.8 vs. 7.5% of SW, respectively) and a higher LTL yield was found in H females than in MS sired females (7.8 vs. 7.3%, resp.).…”
Section: Discussionsupporting
confidence: 88%
“…Generally, growth of an animal is affected by complex mechanisms, acting in para-, endo-and autocrine ways (Migdal et al, 2019) and growth as such is considerably important in rabbit meat production (Blasco et al, 2018). Growth of the new-born rabbit kits depends on the amount of suckled milk, while mainly for a small kit it is important to suck milk immediately after its birth (Szendrö et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…To promote the growth traits of fish, selective breeding may be an effective method under certain conditions [34]. Molecular markers were supposed to promote the accuracy of selection and increase the genetic gain of significant traits [35]. SNP, the third-generation molecular marker, has been widely reported in the genetic breeding of aquaculture animals in recent years [10].…”
Section: Discussionmentioning
confidence: 99%